2021
DOI: 10.3389/fragi.2021.649110
|View full text |Cite|
|
Sign up to set email alerts
|

Key Determinants of Cell-Mediated Immune Responses: A Randomized Trial of High Dose Vs. Standard Dose Split-Virus Influenza Vaccine in Older Adults

Abstract: Background: Efforts to improve influenza vaccine effectiveness in older adults have resulted in some successes, such as the introduction of high-dose split-virus influenza vaccine (HD-SVV), yet studies of cell-mediated immune responses to these vaccines remain limited. We have shown that granzyme B (GrB) activity in influenza A/H3N2 challenged peripheral blood mononuclear cells (PBMC) correlates with protection against influenza following standard dose vaccination (SD-SVV) in older adults. Further, the interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 50 publications
(79 reference statements)
2
8
0
Order By: Relevance
“…Following our discovery of GrB activity in circulating T cells, we found that this bGrB activity increased with age, frailty (Verschoor et al, 2021b) and cytomegalovirus (CMV) seropositivity, and correlated with the frequency of late/ terminally-differentiated, potentially senescent, CD8 + T cells (Haq et al, 2017;McElhaney et al, 2020). A recent study showed that CMV seropositivity in older adults was associated with 1) an increased frequency of CD8 + T cells expressing senescence-associated cell surface markers; 2) lower frequencies of influenza-specific memory T cells; and 3) an enhanced inflammatory response to influenza infection, but no difference in the memory T cell response to influenza infection when compared to seronegative individuals (van den Berg et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Following our discovery of GrB activity in circulating T cells, we found that this bGrB activity increased with age, frailty (Verschoor et al, 2021b) and cytomegalovirus (CMV) seropositivity, and correlated with the frequency of late/ terminally-differentiated, potentially senescent, CD8 + T cells (Haq et al, 2017;McElhaney et al, 2020). A recent study showed that CMV seropositivity in older adults was associated with 1) an increased frequency of CD8 + T cells expressing senescence-associated cell surface markers; 2) lower frequencies of influenza-specific memory T cells; and 3) an enhanced inflammatory response to influenza infection, but no difference in the memory T cell response to influenza infection when compared to seronegative individuals (van den Berg et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…We have also calculated the amount of GrB activity induced with ex vivo stimulation (iGrB) as log (iGrB) log (ex vivo GrB)-log (bGrB) according to our published results from this clinical trial, which showed an age-related decline in iGrB levels in older compared to young adults included as a control group (Verschoor et al, 2021b). Although there were too few LCII cases to determine differences in iGrB levels in H3N2-LCII and No-LCII at 4-weeks post-vaccination, we did observe a poor iGrB response to vaccination in the H3N2-LCII subset but a significant increase in iGrB levels following H3N2 infection (Figure 4), consistent with re-stimulation of CTL memory following infection.…”
Section: Inducible Granzyme B With Ex Vivo Stimulation Following Vaccination and Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also true with respect to acute care and outcomes related to SARS-COV-2 infection [ 6 ], and for certain symptoms of what is commonly referred to as “long-COVID” [ 7 , 8 ]. As observed with SARS-COV-2 [ 9 ], antibody [ 10 ] and cell-mediated [ 11 ] responses to the seasonal influenza vaccine wane with age, as does the effectiveness to prevent hospitalization, although this varies depending on subtype, season, and overall health status [ 12 14 ]. Of the three major influenza (sub)types included in the seasonal vaccine, A/H3N2 breakthrough tends to result in more hospitalizations [ 15 ] and mortality [ 16 ] in older adults, partly due to limited vaccine-induced antibody production [ 17 , 18 ], and especially in years of vaccine mismatch [ 19 ].…”
Section: Introductionmentioning
confidence: 99%